The Impact of Social Marketing Mix and Message Effectiveness to Target Audience Behavior of HIV/Aids - Octavia, A (KnE Social Sciences, 2018)
The purpose of this study is to analyze the effectiveness of social messages delivered by the government to the public about HIV/AIDS, analyze the accuracy of the use of communication media used by the government to convey a message to the community about HIV/AIDS, and analyze the impact of social marketing mix toward target audience behavior. The sample of this study is a community that is accounted for 176 respondents. Analytical tool is Path Analysis. The result shows that social messages conveyed to the public about HIV/AIDS has been effectively using personal communication media. Furthermore, there is a significant direct and indirect social marketing mix toward the behavior of the target audience and through the effectiveness of the message. Keywords: social marketing mix, the effectiveness of the message, the target audience’s behavior